2011
DOI: 10.1371/journal.pcbi.1001051
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of the Stress Induced B-Z Transition in Superhelical DNA

Abstract: We present a method to calculate the propensities of regions within a DNA molecule to transition from B-form to Z-form under negative superhelical stresses. We use statistical mechanics to analyze the competition that occurs among all susceptible Z-forming regions at thermodynamic equilibrium in a superhelically stressed DNA of specified sequence. This method, which we call SIBZ, is similar to the SIDD algorithm that was previously developed to analyze superhelical duplex destabilization. A state of the system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 55 publications
3
41
1
3
Order By: Relevance
“…Antibody binding experiments and SIBZ analysis of this plasmid has shown that it also contains several short Z-forming segments, the longest of which consists of 14 bp [31], [66]. Here we use the BDZ trans algorithm to analyze how these two transitions compete under various conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody binding experiments and SIBZ analysis of this plasmid has shown that it also contains several short Z-forming segments, the longest of which consists of 14 bp [31], [66]. Here we use the BDZ trans algorithm to analyze how these two transitions compete under various conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Several algorithms have been developed to analyze superhelical transitions to a single type of alternate structure in DNA sequences where every base pair is regarded as being able to assume that structure [27][31]. A conformational state is determined by specifying which base pairs are in the B-form state and which are in the alternate structure.…”
Section: Introductionmentioning
confidence: 99%
“…64 Accordingly, in silico analyses showed a high enrichment of these sequences at regulatory regions of the genome and, notably, at the promoters of a wide range of oncogenes. [85][86][87][88] In addition, several conformation-sensitive proteins with regulatory function bind and stabilize non-B DNAs, suggesting an important role of these structures in transcriptional output. 64 Another way to make genetic processes more tolerant to the constrained DNA topology is weakening the DNA through introducing double strand breaks or nicks.…”
Section: Dna Topology and Genome Architecturementioning
confidence: 99%
“…Этот вопрос исследовался при помощи Изинг-подобных подходов [33,35,[234][235][236][237][238][239], а также в радиально-торсионных моделях [175,176,240].…”
Section: теоретические исследования микромеханической денатурации анunclassified
“…Очевидно, создавать нанобиоэлектронные устройства на основе релаксированной ДНК намного проще. Кроме того, открывание пузырьков само по себе способно приводить к частичному сбросу суперспирализационного напряжения [33][34][35]. Это дополнительно затрудняет сравнение расчётных данных с экспериментом.…”
unclassified